The Optimization of Rice Production in Kubu Raya: Input and Allocative Efficiency - Diah Puspita Sari; Adi Suyatno; Novira Kusrini (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Stable and sustainable rice production contributes to the national economy through exports, an important trade commodity for several rice-producing countries. Improving the efficiency and output of the input elements used in rice cultivation is crucial since rice is a staple meal and plays a key role in local economies. This study seeks to identify the input elements that affect lowland rice farming productivity and the degree of allocative efficiency of those inputs. From July 2023 to September 2023, this study was carried out. Using the Accidental sampling method, which involves taking samples that are present or found while conducting research, 88 rice farmers with experience running lowland rice farms in Kuala Dua Village, Sungai Raya, and Kubu Raya were selected as respondents. Land size, labor, seeds, urea fertilizer, NPK fertilizer, Dolomite, pesticide, fungicide, and herbicide are the study variables that make up the production input elements (X9). Allocative efficiency is measured by the marginal product value (NPMXi) or input equal to input price (Pxi), and the data analysis technique employs the Cobb-Douglas analysis methodology with multiple linear regression analysis in SPSS 25.0. An examination of the data shows that the variables, land size, seeds, urea fertilizer, Dolomite, and pesticides all have a role in determining the yield of lowland rice. There is a lack of efficiency in the production elements of land size (X1), seeds (X3), urea fertilizer (X4), Dolomite (X6), and insecticide (X7), as well as labor (X2), NPK fertilizer (X5), fungicides (X8), and herbicides (X9).